THE INTEGRATION OF RAPPORT IN ENGLISH LANGUAGE TEACHING - Abdul Halim (Langkawi: Journal of The Association for Arabic and English, 2015)
This research was intended to notice the finding of what types of rapport builtby the lecturer in teaching speaking and what was the student’ perceptionregarding to rapport established by the lecture in the class. This study useddescriptive qualitative method. The result of this research was expected to bereference for English teachers and or lecturers and students to enhance thequality of teaching and learning English especially how to build a goodrelationship between teacher and or lecturer and students in teaching speakingskill. To obtain the data of this research observation sheet, questionnaire, andinterview were used. These instruments revealed that the lecturer applied allthe observed rapport in this research approriately and got very positiveresponse from the students. In fact all the applied rapport have created goodand friendly atmosphere which stimulate students learn English effectively.Keywords: integration, rapport, English langaue, teaching